Prevalence of community-acquired pneumonia among Egyptian children from rural areas of the Delta region: a single-centre cross-sectional study - Magdy Zedan; Nashwa K. Abousamra; Engy Osman; Asmaa S. Gebril (The Egyptian Journal of Bronchology)
Abstract Background An estimated 1.1–1.4 million children die from pneumonia each year, making up 17–19% of all paediatric mortality; the majority of these deaths occur in underdeveloped nations. In Egypt, during the first 2 years of life, about 6% of children have at least one pneumonic episode. Aims (a) Determination of the prevalence of community-acquired pneumonia (CAP) among children in Egypt’s Delta region, both generally and specifically in rural regions, and (b) evaluation of each case’s clinical and epidemiological phenotypes. Subjects and methods A cross-sectional study was carried out on 174 rural children who were admitted to Mansoura University Children Hospital (MUCH) between 2016 and 2022 and had a confirmed diagnosis of CAP. Two categories were created for the cases: both typical and atypical CAP. Results Out of 39,130 admitted cases, a total of 768 children from Delta region fitted the diagnosis of CAP with an overall prevalence of 1.96% (45.6% from rural areas). Data of 174 cases with CAP were evaluated, and 125 (71.8%) were diagnosed with typical CAP and 49 (28.2%) with atypical CAP. There was a statistically significant difference between typical and atypical CAP groups regarding age and sex. Recurrent pneumonia was significantly more prevalent among children with typical CAP. The prevalence of complications was significantly higher among typical CAP cases compared to atypical CAP cases (P < 0.001). Bronchopneumonia was the most frequent radiologic findings among typical CAP cases (28.0%), while interstitial pneumonia was the most among atypical CAP cases (46.9%). Children with typical CAP had a significantly higher percentage of positive CRP (68.8%) compared to those with atypical CAP (32.7%). Staph coagulase negative was the most identified pathogen among all cases (12.78%). Children with typical CAP had a significantly lower frequency of macrolides use compared to those with atypical CAP (8.8%) vs. (98.0%). Conclusion Among the Delta region, the prevalence of CAP among children is 1.96% (45.6% in rural regions). Compared to atypical CAP, typical CAP affects children more frequently (71.8%) and results in a more severe form of the disease in terms of clinical symptoms, sequelae, and radiological abnormalities.